2005
DOI: 10.1084/jem.20050137
|View full text |Cite
|
Sign up to set email alerts
|

Differential contributions of central and effector memory T cells to recall responses

Abstract: Although the absolute number of memory CD8+ T cells established in the spleen following antigen encounter remains stable for many years, the relative capacity of these cells to mediate recall responses is not known. Here we used a dual adoptive transfer approach to demonstrate a progressive increase in the quality of memory T cell pools in terms of their ability to proliferate and accumulate at effector sites in response to secondary pathogen challenge. This temporal increase in efficacy occurred in CD62Llo (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
275
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(290 citation statements)
references
References 48 publications
15
275
0
Order By: Relevance
“…Further analysis of CD8 + T cell phenotype showed that there was no difference within percentage of Tcm and Tem/Teff cells between the different PLGA NP immunized groups, but an enhanced ratio of CD8 + T cells with CD44 int phenotype was detected in mice immune to rLM-OVA challenge. Thus, although no clear definition of CD44 int CD62L neg is available [48][49][50], we show a correlation between their presence and intradermal immunization-induced protective immunity to challenge with rLM-OVA.…”
Section: Discussionmentioning
confidence: 56%
“…Further analysis of CD8 + T cell phenotype showed that there was no difference within percentage of Tcm and Tem/Teff cells between the different PLGA NP immunized groups, but an enhanced ratio of CD8 + T cells with CD44 int phenotype was detected in mice immune to rLM-OVA challenge. Thus, although no clear definition of CD44 int CD62L neg is available [48][49][50], we show a correlation between their presence and intradermal immunization-induced protective immunity to challenge with rLM-OVA.…”
Section: Discussionmentioning
confidence: 56%
“…Most would accept that a proportion of the T CM precursors must have the capacity to become fully functional effector and͞or T EM cells after secondary challenge (4,5,14). Some studies support the view that a T EM 3T CM transition is possible, both during the acute response and in long-term memory (4,14).…”
mentioning
confidence: 91%
“…Current thinking is focused on the idea that both human and mouse memory T cells can be classified into distinct central memory (T CM ) and effector memory (T EM ) sets (1)(2)(3)(4)(5). Whereas the T CM lymphocytes are CD62L hi , which means that these T cells transit directly from blood to lymph nodes via the high endothelial venules (6,7), the more ''activated'' CD62L lo T EM set accesses the nodes only via afferent lymph and is widely dispersed in a broad range of somatic tissues (8,9).…”
mentioning
confidence: 99%
“…T CM are an earlier stage of differentiation and therefore possess superior qualities enabling them to better fight microbial challenges and mediate therapeutic antitumor immunity when compared to T EM , which in turn are superior to the terminally differentiated effector cells (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%